The Dynamics of Crises and the Equity Premium - Branger, Nicole; Kraft, Holger; Meinerding, Christoph (Review of Financial Studies, 2016)
It is a major challenge for asset pricing models to generate a high equity premium and a low risk-free rate while imposing realistic consumption dynamics. To address this issue, our paper proposes a novel pricing channel: we allow for consumption drops that can spark an economic crisis. This new feature generates a large equity premium even if possible consumption drops are of moderate size. In turn, our model also matches the consumption data of 42 countries along several dimensions. In particular, our approach generates a realistic number of crises that have realistic durations and involve clustering of moderate consumption drops. Received October 17, 2014; accepted August 18, 2015 by Editor Pietro Veronesi.